O programa permanência e êxito no Instituto Federal Farroupilha: trabalho pedagógico e fracasso escolar - Silveira, Rozieli Bovolini (2017)
The present research discusses the possibility of the permanence and the successful conclusion of the students of the working class, who access the Professional and Technological Education. This discussion was based on the analysis of the Permanence and Success Program (PPE), developed by the Federal Institute Farroupilha. The research is linked to the research line of Policy and Management in EPT of the Master in Professional and Technological Education of the Federal University of Santa Maria and the Kairós Group - Group of Researches and Studies on Work, Education and Public Policies. After the presentation of the research and the theoretical-methodological routings, this dissertation will be composed of five chapters. In the first instance, previous research on the permanence and success, school failure, evasion and retention in Professional and Technological Education is presented. After this, the historicity of educational policies for Professional and Technological Education, from the 1990s to the National Education Plan approved in 2014, is dealt with. The next chapter begins with the analysis of the category of Work and the relationship with Education. It also presents the Pedagogical Work category and the initial relations with this research data production. The last chapters deal more intensively with the institutional policy of permanence and success of the IF Farroupilha and the relations in Pedagogical Work. The analysis took place, from the elaboration stage, on the motivations for creating the program until the implementation phase. As part of a material historical reality, that comes from a praxis, this research had as methodological foundation, historical dialectical materialism. Interviews were carried out with the PPE Coordinators and the Technological Axes of Júlio de Castilhos and São Vicente do Sul Campi, as well as documentary analysis and on-site observations that were registered in the field record book. In addition, the students of the Integrated and Subsequent Courses were invited to answer a questionnaire about education at IF Farroupilha. The selected campuses had as a clipping the geographical area and the Expansion phase of the Federal Network of Professional and Technological Education. From the data production, it was possible to perceive that there is a dualism of conceptions about Professional and Technological Education and different positions about permanence and success. Although the educational policy, that rules the Federal Institutes, is marked by inclusion and social justice, reality shows that there are still exclusion and elimination movements. In addition, it was possible to analyze that the link in Pedagogical Work is marked by affective distancing and disciplining, although there were host movements.